2004
DOI: 10.1046/j.1471-4159.2003.02247.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile of the nucleus accumbens of human cocaine abusers: evidence for dysregulation of myelin

Abstract: Chronic cocaine abuse induces long-term neural adaptations as a consequence of alterations in gene expression. This study was undertaken to identify those transcripts differentially regulated in the nucleus accumbens of human cocaine abusers. Affymetrix microarrays were used to measure transcript abundance in 10 cocaine abusers and 10 control subjects matched for age, race, sex, and brain pH. As expected, gene expression of cocaine-and amphetamine-regulated transcript (CART) was increased in the nucleus accumb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
183
1
2

Year Published

2004
2004
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(200 citation statements)
references
References 45 publications
12
183
1
2
Order By: Relevance
“…The decrease in MBP preceded the decrease in NFH, leading the authors to conclude that the change in myelin is the primary pathological event in cerebral WM under chronic hypoperfusion. Relatedly, a gene expression study of the nucleus accumbens in cocaine users found a reduction in the expression of myelinrelated genes (Albertson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in MBP preceded the decrease in NFH, leading the authors to conclude that the change in myelin is the primary pathological event in cerebral WM under chronic hypoperfusion. Relatedly, a gene expression study of the nucleus accumbens in cocaine users found a reduction in the expression of myelinrelated genes (Albertson et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A recent unbiased gene-array study with subsequent target validation by real-time quantitative polymerase chain reaction (Q-PCR) led to the identification of cocaine-induced altered expression in the NAc of multiple genes, including a group of myelin-related proteins that is involved in establishment and maintenance of myelin sheaths [25]. Altered myelin-associated gene expression has also been associated with excessive alcohol consumption in human alcoholic brain [26][27][28] and in animals treated chronically with ethanol [29].…”
Section: Introductionmentioning
confidence: 99%
“…Myelin in the CNS, which exists as compact and non-compact forms, is essential for nervous system function. We have included molecules that were previously identified as abnormally expressed in NAc [18,25], as well as six additional white matter-related transcripts that have previously been found to be abnormally regulated in other neuropsychiatric illnesses, including schizophrenia [38][39][40][41][42]. Although these myelin proteins presently are not well characterized, they can be divided into two groups; a group of transmembrane glycoproteins, which include the MOBP, PLP1, CLDN-11, EDG2 and MAG molecules and a group of cytosolic proteins consisting of the MBP, CNP, QKI and transferrin proteins [43].…”
Section: Introductionmentioning
confidence: 99%
“…The microarray method allows high-throughput analysis of gene expression patterns (Khan et al, 1999;Lipshutz et al, 1999), and it is particularly useful for studying cocaineinduced gene expression changes (Bibb et al, 2001;Freeman et al, 2001a, b;Toda et al, 2002;McClung and Nestler, 2003;Yuferov et al, 2003;Tang et al, 2003;Yao et al, 2004;Albertson et al, 2004). Despite these studies, the gene expression profile induced by chronic cocaine through the DA D1 receptors remains unclear.…”
Section: Introductionmentioning
confidence: 99%